Method for preparing transition layer of accelerator neutron source lithium target by electrodeposition-magnetron sputtering
The rough copper deposition layer was formed by electrochemical deposition, and the transition layer was deposited by magnetron sputtering technology, which solved the problem of cracking and falling off of the neutron source target film on the substrate surface, and achieved high binding and low stress film deposition, improving the The stability of the target material is achieved.
Patent Information
- Application Number
- CN202411426016.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-14
AI Technical Summary
Neutron source targets are susceptible to radiation damage and material fatigue during long-term operation, causing the film to crack and fall off on the substrate surface, affecting the cooling effect and the performance of the target material.
A rough copper deposition layer is formed on the surface of the copper substrate by electrochemical deposition, and a transition layer is deposited using magnetron sputtering technology to reduce the internal stress between the film and the substrate and improve the binding force.
A uniform deposition of transition layers on the surface of complex-shaped copper substrates is achieved, which reduces the stress and cracking risks of the film and improves the stability and performance of the target material.
Smart Images

Figure CN118957584B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of neutron source targets, and in particular to a method for preparing a transition layer of an accelerator neutron source lithium target by electro-deposition-magnetron sputtering. Background Art
[0002] Boron Neutron Capture Therapy (BNCT) is a 10 An advanced radiotherapy technology designed based on the principle of large neutron absorption cross section of B isotope. 10 B(n, α) 7 Li nuclear reactions produce high-energy particles with an extremely short range (<10μm) that accurately destroy tumor cells. Neutron capture drugs and neutron sources, as the two core elements of BNCT, are crucial to the final therapeutic effect. At present, there are two suitable sources of neutron beams in the world. One is to obtain neutron beams through reactors, and the other is to obtain them through accelerator neutron sources. Accelerator-based neutron sources produce neutron beams by interacting with accelerated particles (such as protons or deuterons) with target materials. Compared with traditional nuclear reactors, it can provide more precise and directional neutron beams and control the energy and flux of generated neutrons. And due to its advantages in radiation safety, operational flexibility and operation and maintenance costs, accelerator neutron sources have become one of the preferred technologies in many research fields, especially in clinical medicine.
[0003] Neutron source targets are key components that convert high-energy particle beams generated by accelerators into high-flux neutron sources. They are affected by radiation damage and material fatigue during long-term operation. Therefore, the selection and design of neutron source targets are crucial. Neutron source target systems generally use lithium or beryllium as the main nuclear reaction layer to maximize the production of neutrons. At the same time, the target system needs to have good thermal and mechanical properties to withstand the heat and stress generated by high-energy particle impacts. Most protons produce bubbles when they pass through the lithium layer and are deposited on the surface of the copper substrate, which in turn causes hydrogen embrittlement, affects the cooling effect, and accelerates the degradation of target material performance.
[0004] Tantalum has a high hydrogen diffusion coefficient and can be used as a transition layer in the target system of accelerator boron neutron capture therapy (AB-BNCT). There are many methods for preparing Ta films, such as vacuum plasma spraying (VPS), chemical vapor deposition (CVD) and physical vapor deposition (PVD). Compared with the above methods, magnetron sputtering is the best choice due to its advantages such as fast sputtering speed, large deposition area, dense and uniform film, and excellent adhesion. However, a Ta film thickness of 20μm can effectively prevent proton deposition and hydrogen embrittlement in the Cu substrate, and the physical properties of Ta are very different from those of the substrate copper. When the magnetron sputtering deposited film reaches a certain thickness, the film cracks and falls off due to stress accumulation.
[0005] The film is prone to cracking and falling off on the substrate surface, which may be caused by multiple factors, such as improper deposition conditions, poor compatibility between the substrate and the film, and large internal stress in the film. Changing the interaction between the substrate material and the film is one of the angles to relieve the film stress. Increasing the roughness of the Cu substrate can delay the formation of a continuous structure of Ta particles on the surface of the copper substrate, reduce the stress during the film growth process, and increase the adhesion of the film. The substrate surface is often roughened by physical or chemical methods (sandblasting, mechanical polishing or chemical etching), or a layer of material with good adhesion (such as titanium, chromium, etc.) is introduced between the substrate and the film by magnetron sputtering as an adhesion layer to improve the adhesion of the film. However, the above methods have their own defects. For example, it is difficult to achieve uniform treatment on the surface of a complex-shaped substrate by mechanical roughening methods (such as sandblasting and polishing). The reason is that sandblasting, mechanical polishing and other methods can only roughen the contacted surface when treating irregular substrates, but it is difficult to take into account the local parts with tiny fine structures such as through holes; and when the adhesion layer is introduced between the substrate and the film, the sputtering target needs to be replaced, and pre-sputtering will cause waste of target material. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a transition layer of an accelerator neutron source lithium target by electro-deposition-magnetron sputtering. The present invention firstly performs surface treatment on a copper substrate by electrochemical deposition, and a rough copper deposition layer can be constructed on the surface of the copper substrate. The method can be applied to copper substrates of various shapes; on this basis, the present invention further uses magnetron sputtering technology to deposit a transition layer on the rough substrate surface, and the internal stress between the obtained transition layer and the substrate is small and the bonding force is high.
[0007] The specific technical solution of the present invention is: a method for preparing an accelerator neutron source lithium target transition layer by electrodeposition-magnetron sputtering, comprising the following steps:
[0008] 1) The copper substrate is used as the cathode and the copper sheet is used as the anode, which are placed in an electrolyte for electrochemical deposition to form a copper deposition layer with a rough surface on the surface of the copper substrate.
[0009] 2) Constructing a transition layer on the surface of the copper deposited layer by magnetron sputtering.
[0010] In the above method, the present invention firstly performs surface treatment on the copper substrate by electrochemical deposition, and a rough copper deposition layer can be deposited on the surface of the copper substrate, and then a transition layer is constructed on the surface of the rough copper deposition layer by magnetron sputtering technology. On the one hand, since the copper substrate and the copper deposition layer are both copper, they have the same lattice structure and thermal expansion coefficient, so the interface between the two has a high interface matching degree and low internal stress, and the copper deposition layer can be firmly bonded to the surface of the copper substrate; on the other hand, since the copper deposition layer has an ideal rough surface, the transition layer and the copper substrate also have low internal stress and high bonding force.
[0011] Compared with the physical or chemical methods such as sandblasting, mechanical polishing or chemical etching to roughen the copper substrate surface in the prior art, the method of the present invention can be applied to copper substrates of various complex shapes, and is not limited by the shape of the copper substrate; compared with the method of introducing an adhesion layer (such as titanium, chromium, etc.) between the copper substrate and the transition layer by magnetron sputtering to improve the adhesion of the transition layer in the prior art, the electrochemical deposition method of the present invention does not need to replace the sputtering target, which will not cause waste of target materials; on the other hand, it will not introduce additional element impurities. In addition, the method of the present invention can flexibly change the electrochemical deposition parameters (current density, deposition time) according to the needs, so that the surface roughness of the copper substrate can be accurately controlled to achieve the desired surface characteristics.
[0012] Preferably, in 1), the copper deposition layer has a thickness of 0.05-0.5 μm and a surface roughness of 40-100 nm.
[0013] Preferably, in 1), the copper substrate is pre-ground, polished, cleaned and dried.
[0014] Preferably, in 1), the electrolyte comprises 0.05-0.1 mol / L CuSO 4 ·5H 2 O, 0.05-0.1 mol / LNaCl, 0.01-0.1 mol / LH 3 BO 3 , 0.01-0.1 mol / LC 12 H 25 SO 4 Na and water.
[0015] In the electrolyte of the present invention, CuSO 4 ·5H 2 O is the main salt of the electrochemical deposition solution, providing the main metal ions. If the main salt concentration is too low, it will cause the coating to burn. If the concentration is too high, the deposition rate will be faster, which will lead to a decrease in the bonding strength of the coating. The chloride ions in NaCl are beneficial for electrons to be directed from the electrode to the copper ions, increase the copper ion concentration on the cathode surface, and promote the growth of crystal nuclei. They can also activate the copper anode and help it dissolve evenly. Without the effect of chloride ions, the leveling performance and brightness of the plating solution will decrease. 3 BO 3 It is a pH buffer for the plating solution, which can increase the conductivity of the plating solution and keep it in a weakly acidic state. 12 H 25 SO 4 As an additive, Na can accelerate the deposition of metallic copper ions through the synergistic effect with chloride ions, and can refine the grains, making the coating bright and delicate. However, if too much is added, the coating will become white and brittle.
[0016] Preferably, in 1), the conditions of the electrochemical deposition are: the power supply is in constant current mode, the deposition temperature is 25-40°C, and the stirring speed is 200-600 r·min -1 , the current density is 15-25 mA·cm -2 , the deposition time is 20-40 min.
[0017] Preferably, in 1), the copper substrate is cleaned and dried after the electrochemical deposition.
[0018] Preferably, in 2), the transition layer is a Ta transition layer or a multi-concentration V-Ta transition layer. In order to solve the problem that the target material easily absorbs protons inside the metal during use, resulting in brittle fracture, a transition layer (anti-hydrogen embrittlement layer) can be provided between the copper substrate and the target layer.
[0019] Preferably, in the multi-concentration V-Ta transition layer, the Ta content increases linearly or stepwise in the range of 10-100wt% from the copper substrate to the target layer.
[0020] At present, the material of the transition layer (anti-hydrogen embrittlement layer) is usually V or Ta. A single vanadium layer or a single tantalum layer needs to be thicker to effectively avoid hydrogen embrittlement. When the metal film formed by magnetron sputtering is thick, stress is easily deposited, which causes the film to crack or fall off. The present invention finds that using a V-Ta composite material as a transition layer and controlling the Ta content to increase gradually from the copper substrate to the target layer within the above-mentioned specific range can maintain a low stress when the transition layer is thicker, thereby reducing the risk of cracking or falling off of the transition layer.
[0021] Preferably, the multi-concentration V-Ta transition layer is prepared by magnetron co-sputtering. The transition layer of the present invention is obtained by a magnetron co-sputtering process. The difference between the film prepared by the magnetron co-sputtering process and the traditional single coating is that its atomic arrangement is more chaotic. In the magnetron co-sputtering process, each element is interrupted by the second element before forming a continuous film. The higher the degree of chaos, the denser the atomic stacking, and the more grain boundaries are formed. During the deposition process, the film can relax strain by forming interfaces, dislocations or other defects, so stress can also be better released.
[0022] Preferably, the thickness of the tantalum transition layer or the multi-concentration V-Ta transition layer is 15-40 microns. The thickness of the multi-concentration V-Ta transition layer of the present invention is comparable to that of a conventional transition layer, but can effectively reduce the stress of the transition layer and reduce the risk of cracking or falling off.
[0023] Compared with the prior art, the beneficial effects of the present invention are:
[0024] (1) The present invention performs surface treatment on a copper substrate by an electrochemical deposition method, depositing a rough copper deposition layer on the surface of the copper substrate, and then depositing a transition layer on the rough substrate surface by magnetron sputtering technology. The internal stress between the obtained transition layer and the substrate is small and the bonding force is high.
[0025] (2) Compared with the prior art method of roughening the surface of the copper substrate by physical or chemical methods such as sandblasting, mechanical polishing or chemical etching, the intermediate layer prepared by the method of the present invention is more uniform and can be applied to copper substrates of various complex shapes, thus not being restricted by the shape of the copper substrate.
[0026] (3) Compared with the prior art method of introducing an adhesion layer (such as titanium, chromium, etc.) between the copper substrate and the transition layer by magnetron sputtering to improve the adhesion of the transition layer, the electrochemical deposition method of the present invention does not require the replacement of the sputtering target, which will not cause waste of target materials; on the other hand, it does not introduce additional element impurities.
[0027] (4) The method of the present invention can flexibly change the electrochemical deposition parameters (current density, deposition time) according to the needs, so as to accurately control the surface roughness of the copper substrate to achieve the desired surface properties.
[0028] (5) The present invention further preferably uses a V-Ta composite material as a transition layer, and controls the Ta content to increase gradually from the substrate to the target layer within a specific range, so that the transition layer can still have a lower stress when it is thicker, thereby effectively avoiding the cracking or shedding of the transition layer; the present invention constructs a multi-concentration V-Ta transition layer on the substrate surface through a magnetron co-sputtering process. Compared with traditional coating processes, magnetron co-sputtering can obtain a transition layer with lower stress. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the principle of electrochemical deposition pretreatment of copper substrate.
[0030] Figure 2 This is a scanned image of the copper substrate surface after electrochemical deposition in Example 1 of the present invention.
[0031] Figure 3 This is a distribution diagram of Cu elements on the surface of the copper substrate after electrochemical deposition in Example 1 of the present invention.
[0032] Figure 4 This is a scanned image of the tantalum transition layer obtained after magnetron sputtering in Example 1 of the present invention.
[0033] Figure 5 This is a Ta element distribution diagram of the tantalum transition layer obtained after magnetron sputtering in Example 1 of the present invention.
[0034] Figure 6These are photos of the planar copper substrates after coating in Examples 1-3 and Comparative Examples 1-4.
[0035] Figure 7 The actual image (left) and structural schematic diagram (right) of the copper substrate with a mesh-structured surface in Example 4.
[0036] Figure 8 This is a photograph of the copper substrate with a mesh-structured surface after electrochemical deposition of a copper deposition layer in Example 4. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the embodiments.
[0038] A method for preparing an accelerator neutron source lithium target transition layer by electrodeposition-magnetron sputtering comprises the following steps:
[0039] 1) The copper substrate is used as the cathode and the copper sheet is used as the anode. They are placed in an electrolyte for electrochemical deposition to form a copper deposition layer with a rough surface on the surface of the copper substrate. The principle is as follows: Figure 1 shown.
[0040] In some preferred implementation cases, in step 1), the copper substrate is pre-ground, polished, cleaned, and dried.
[0041] In some preferred implementation cases, in step 1), the electrolyte includes 0.05-0.1 mol / L CuSO 4 ·5H 2 O, 0.05-0.1 mol / L NaCl, 0.01-0.1 mol / LH 3 BO 3 , 0.01-0.1 mol / LC 12 H 25 SO 4 Na and water.
[0042] In some preferred implementation cases, in step 1), the conditions of the electrochemical deposition are: the power supply is in constant current mode, the deposition temperature is 25-40°C, and the stirring speed is 200-600 r·min -1 , the current density is 15-25 mA·cm -2 , the deposition time is 20-40 min.
[0043] In some preferred implementation cases, in step 1), the copper deposition layer has a thickness of 0.05-0.5 μm and a surface roughness of 40-100 nm.
[0044] In some preferred implementation cases, in step 1), the copper substrate is cleaned and dried after electrochemical deposition.
[0045] 2) Constructing a transition layer on the surface of the copper deposited layer by magnetron sputtering.
[0046] In some preferred implementation cases, in step 2), the transition layer is a tantalum transition layer or a multi-concentration V-Ta transition layer. In the multi-concentration V-Ta transition layer, the Ta content increases linearly or stepwise in the range of 10-100wt% from the copper substrate to the target layer.
[0047] In some more preferred implementation cases, the thickness of the tantalum transition layer or the multi-concentration V-Ta transition layer is 15-40 microns.
[0048] In some more preferred implementation cases, the multi-concentration V-Ta transition layer is formed by stacking multiple layers of V-Ta films in a step-by-step manner. Further, the multi-concentration V-Ta transition layer is formed by stacking a low Ta concentration V-Ta film, a medium Ta concentration V-Ta film, and a high Ta concentration V-Ta film; and the Ta contents in the low Ta concentration V-Ta film, the medium Ta concentration V-Ta film, and the high Ta concentration V-Ta film are 10-30wt%, 30-60wt%, and 60-90wt%, respectively. The present invention finds that in a step-by-step manner, the multi-concentration V-Ta transition layer is designed as a three-layer step-by-step structure, and the Ta concentrations in the three layers of film are limited to the above ranges, respectively, which has the best effect on reducing the stress of the transition layer.
[0049] In some more preferred implementation cases, the thickness of the low Ta concentration V-Ta film is 1-2 microns, the thickness of the medium Ta concentration V-Ta film is 10-15 microns, and the thickness of the high Ta concentration V-Ta film is 3-9 microns. The present invention designs the thickness of the low concentration layer to be the thinnest, the medium concentration layer to be the thickest, and the thickness of the high concentration layer to be in the middle because: when protons of a certain energy are injected into the target surface, their distribution in the transition layer is uneven, the low concentration layer is the thinnest, and the protons can be slowed down first, while the medium concentration layer is the thickest, and can absorb and accommodate most of the protons, and the high concentration layer is in the middle, which blocks the remaining protons from continuing to diffuse into the matrix.
[0050] The preparation method of the above-mentioned multi-concentration V-Ta transition layer with step-by-step increase includes:
[0051] S1: Fix the Ta target and the V target on two target positions; fix the substrate on the mobile fixture trolley;
[0052] S2: The sputtering powers of the Ta target and the V target are adjusted to 50-100W and 100-300W respectively, and magnetron co-sputtering is performed in an inert atmosphere. The mobile fixture carriage is controlled to move back and forth between the Ta target and the V target at a rate of 10-15mm / s. After coating, a low Ta concentration V-Ta film is formed;
[0053] S3: adjusting the sputtering powers of the Ta target and the V target to 100-300W and 100-300W respectively, and the trolley speed to 15-20mm / s, to form a V-Ta film with a medium Ta concentration;
[0054] S4: The sputtering powers of the Ta target and the V target are adjusted to 300-600W and 100-300W respectively, and the carriage speed is 20-25mm / s to form a high Ta concentration V-Ta film.
[0055] The present invention uses magnetron co-sputtering to ionize an inert gas such as argon under the action of an electric field, and the ionized argon ions bombard the surfaces of the Ta target and the V target, and the target material sputters a large number of target material atoms and deposits them on the surface of the substrate. Specifically, in the above-mentioned magnetron co-sputtering process, the present invention mainly constructs a multi-concentration V-Ta transition layer with a step-by-step increase in Ta content by differentially setting the sputtering power.
[0056] In addition, the present invention finds that the trolley rate has an important influence on the degree of disorder of Ta and V atoms in each layer of the film and the physical structure of the film. As mentioned above, the atomic arrangement in the film produced by the magnetron co-sputtering process is more chaotic. In the magnetron co-sputtering process, each element is interrupted by the second element before forming a continuous film. The higher the degree of disorder, the denser the atomic stacking, the more grain boundaries formed, and the better the stress release. Therefore, in theory, the higher the trolley rate, the higher the degree of disorder of Ta and V atoms.
[0057] The present invention sets the trolley rate of the low Ta concentration layer at the slowest (i.e., the lowest atomic disorder), the medium Ta concentration layer at the middle (i.e., the atomic disorder is middle), and the high Ta concentration layer at the fastest (i.e., the atomic disorder is highest) because: the trolley rate is set to the slowest in the low Ta concentration layer, so that the coating can be approximately regarded as alternating coating of two elements. This layer is connected to the substrate, and the multilayer film has a higher bonding force with the substrate than a single film; the medium Ta concentration layer trolley rate is set to the middle, because a large number of protons are distributed in this area, the atomic disorder is increased, more heterogeneous interfaces are provided, and a large number of hydrogen protons can be absorbed; and the high Ta concentration layer trolley rate is set to the fastest. When the film is deposited to a certain thickness, it is easily affected by stress and cracks, while the moving speed is higher, the atomic disorder is high, the grain boundary density is high, and thus the stress is small, and the film is not easy to crack.
[0058] The preparation method of the linearly increasing multi-concentration V-Ta transition layer includes:
[0059] S1: Install the Ta target and the V target on the two target positions of the magnetron sputtering coating machine respectively; fix the substrate on the mobile fixture trolley, pass inert gas into the sputtering chamber, and close the sputtering chamber.
[0060] S2: Adjust the initial sputtering power of the Ta target to 50-100W, the power increase rate to 50~100W / h, the initial sputtering power of the V target to 100-300W, the power increase rate to 20-50W / h, perform magnetron co-sputtering in an inert atmosphere, control the mobile fixture trolley to move back and forth between the Ta target and the V target at an initial rate of 10-15mm / s and an increase rate of 1.5-2.5mm / h, and after coating, form a multi-concentration V-Ta transition layer.
[0061] Different from the step-by-step preparation process, when the Ta content in the transition layer increases linearly, the present invention correspondingly adopts the above-mentioned process of linearly increasing sputtering power and synchronously linearly increasing trolley speed to construct a multi-concentration V-Ta transition layer.
[0062] Specific examples and comparative examples.
[0063] Example 1 (the transition layer is a tantalum transition layer)
[0064] A method for preparing an accelerator neutron source lithium target transition layer by electrodeposition-magnetron sputtering, specifically comprising the following steps:
[0065] (1) Electrochemical deposition of copper deposit:
[0066] (1.1) Using 0.1 mol·L -1 CuSO 4 ·5H 2 O as raw material, and 0.1 mol·L -1 NaCl, 0.05 mol·L -1 H 3 BO 3 , 0.05 mol·L -1 C 12 H 25 SO 4 Na and water together form the electrolyte for standby use;
[0067] (1.2) Select a flat copper substrate with a surface size of 10*10*1 mm, grind, polish, clean and dry it for later use;
[0068] (1.3) The copper substrate was used as the cathode and the copper foil was used as the anode. They were placed in the electrolyte. The power supply was fixed to the constant current mode. The deposition temperature was set to 30 °C and the stirring speed was set to 400 r·min. -1 , the current density was set to 20 mA·cm -2 Electrochemical deposition was carried out for 30 min, and the surface roughness of the obtained copper deposition layer was 60.85 nm and the thickness was 0.1 μm.
[0069] (1.4) The deposited copper substrate is cleaned and dried for later use.
[0070] Figure 2 This is a scanned image of the copper substrate surface after electrochemical deposition in Example 1 of the present invention. Figure 3 This is a distribution diagram of Cu elements on the surface of the copper substrate after electrochemical deposition in Example 1 of the present invention. The surface of the copper substrate after electrodeposition presents a spherical morphology, a rough surface, voids, and a uniform distribution of Cu elements.
[0071] (2) Preparation of tantalum transition layer by magnetron sputtering:
[0072] (2.1) Target pretreatment: The Ta target was installed in the first target position of the magnetron sputtering coating machine; the copper substrate treated in step (1) was fixed on the substrate table and then fixed on the sample trolley. The sputtering chamber was closed and low vacuum was first extracted. When the pressure in the sputtering chamber reached below 4 Pa, the molecular pump was started to extract high vacuum. When the vacuum in the sputtering chamber reached 5×10 -8 After Pa, argon gas is introduced for pre-sputtering to remove contaminants on the target surface;
[0073] (2.2) Coating: Adjust the gas pressure in the sputtering chamber, adjust the sputtering power of the Ta target to 300 W, the duty cycle to 90%, the bias voltage to -150 V, and the sputtering gas pressure to 0.5 Pa, and perform sputtering coating for 20 h (pause for cooling for 2 h every 5 h). After the sputtering is completed, turn off the magnetron and take out the substrate stage to obtain a copper substrate with a tantalum transition layer (thickness of 21 μm) deposited on it.
[0074] Figure 4 This is a scanned image of the tantalum transition layer obtained after magnetron sputtering in Example 1 of the present invention. Figure 5 This is a Ta element distribution diagram of the tantalum transition layer obtained after magnetron sputtering in Example 1 of the present invention. Figure 4-5 It is shown in the figure that Ta covers the surface of the copper substrate well and fills into the gaps in the copper deposition layer, with a relatively uniform distribution on the surface.
[0075] Comparative Example 1
[0076] Comparative Example 1 is different from Example 1 only in that no copper deposition layer is deposited on the surface of the copper substrate, and specifically comprises the following steps:
[0077] (1) A planar copper substrate with a surface size of 10*10*1 mm (same as in Example 1) was selected, and was ground, polished, cleaned, and dried for later use.
[0078] (2) Preparation of tantalum transition layer by magnetron sputtering:
[0079] (2.1) Target pretreatment: The Ta target was installed in the first target position of the magnetron sputtering coating machine; the copper substrate treated in step (1) was fixed on the substrate table and then fixed on the sample trolley. The sputtering chamber was closed and low vacuum was first extracted. When the pressure in the sputtering chamber reached below 4 Pa, the molecular pump was started to extract high vacuum. When the vacuum in the sputtering chamber reached 5×10 -8 After Pa, argon gas is introduced for pre-sputtering to remove contaminants on the target surface;
[0080] (2.2) Coating: Adjust the gas pressure in the sputtering chamber, adjust the sputtering power of the Ta target to 300 W, the duty cycle to 90%, the bias voltage to -150 V, and the sputtering gas pressure to 0.5 Pa, and perform sputtering coating for 20 h (pause for cooling for 2 h every 5 h). After the sputtering is completed, turn off the magnetron and take out the substrate stage to obtain a copper substrate with a tantalum transition layer (thickness of 21 μm) deposited on it.
[0081] Comparative Example 2
[0082] Comparative Example 2 is different from Example 1 only in that the electrolyte in step (1.1) contains CuSO 4 ·5H 2 O concentration is 0.15 mol·L -1 , specifically including the following steps:
[0083] (1) Electrochemical deposition of copper deposit:
[0084] (1.1) Using 0.15 mol·L -1 CuSO 4 ·5H 2 O as raw material, and 0.1 mol·L -1 NaCl, 0.05 mol·L -1 H 3 BO 3 , 0.05 mol·L -1 C 12 H 25 SO 4 Na and water together form the electrolyte for standby use;
[0085] (1.2) Select a flat copper substrate with a surface size of 10*10*1 mm (same as in Example 1), grind, polish, clean and dry it for later use;
[0086] (1.3) The copper substrate was used as the cathode and the copper foil was used as the anode. They were placed in the electrolyte. The power supply was fixed to the constant current mode. The deposition temperature was set to 30 °C and the stirring speed was set to 400 r·min. -1 , the current density was set to 20 mA·cm -2Electrochemical deposition was carried out for 30 min, and the surface roughness of the copper deposit obtained was 74.28 nm and the thickness was 0.18 μm.
[0087] (1.4) The deposited copper substrate is cleaned and dried for later use.
[0088] (2) Preparation of tantalum transition layer by magnetron sputtering:
[0089] (2.1) Target pretreatment: The Ta target was installed in the first target position of the magnetron sputtering coating machine; the copper substrate treated in step (1) was fixed on the substrate table and then fixed on the sample trolley. The sputtering chamber was closed and low vacuum was first extracted. When the pressure in the sputtering chamber reached below 4 Pa, the molecular pump was started to extract high vacuum. When the vacuum in the sputtering chamber reached 5×10 -8 After Pa, argon gas is introduced for pre-sputtering to remove contaminants on the target surface;
[0090] (2.2) Coating: Adjust the gas pressure in the sputtering chamber, adjust the sputtering power of the Ta target to 300 W, the duty cycle to 90%, the bias voltage to -150 V, and the sputtering gas pressure to 0.5 Pa, and perform sputtering coating for 20 h (pause for cooling for 2 h every 5 h). After the sputtering is completed, turn off the magnetron and take out the substrate stage to obtain a copper substrate with a tantalum transition layer (thickness of 21 μm) deposited on it.
[0091] Comparative Example 3
[0092] Comparative Example 3 is different from Example 1 only in that the electrolyte in step (1.1) contains CuSO 4 ·5H 2 O concentration is 0.03 mol·L -1 , specifically including the following steps:
[0093] (1) Electrochemical deposition of copper deposit:
[0094] (1.1) Using 0.03 mol·L -1 CuSO 4 ·5H 2 O as raw material, and 0.1 mol·L -1 NaCl, 0.05 mol·L -1 H 3 BO 3 , 0.05 mol·L -1 C 12 H 25 SO 4 Na and water together form the electrolyte for standby use;
[0095] (1.2) Select a flat copper substrate with a surface size of 10*10*1 mm (same as in Example 1), grind, polish, clean and dry it for later use;
[0096] (1.3) The copper substrate was used as the cathode and the copper foil was used as the anode. They were placed in the electrolyte. The power supply was fixed to the constant current mode. The deposition temperature was set to 30 °C and the stirring speed was set to 400 r·min. -1 , the current density was set to 20 mA·cm -2 Electrochemical deposition was carried out for 30 min, and the surface roughness of the copper deposit obtained was 53.85 nm and the thickness was 0.08 μm.
[0097] (1.4) The deposited copper substrate is cleaned and dried for later use.
[0098] (2) Preparation of tantalum transition layer by magnetron sputtering:
[0099] (2.1) Target pretreatment: The Ta target was installed in the first target position of the magnetron sputtering coating machine; the copper substrate treated in step (1) was fixed on the substrate table and then fixed on the sample trolley. The sputtering chamber was closed and low vacuum was first extracted. When the pressure in the sputtering chamber reached below 4 Pa, the molecular pump was started to extract high vacuum. When the vacuum in the sputtering chamber reached 5×10 -8 After Pa, argon gas is introduced for pre-sputtering to remove contaminants on the target surface;
[0100] (2.2) Coating: Adjust the gas pressure in the sputtering chamber, adjust the sputtering power of the Ta target to 300 W, the duty cycle to 90%, the bias voltage to -150 V, and the sputtering gas pressure to 0.5 Pa, and perform sputtering coating for 20 h (pause for cooling for 2 h every 5 h). After the sputtering is completed, turn off the magnetron and take out the substrate stage to obtain a copper substrate with a tantalum transition layer (thickness of 21 μm) deposited on it.
[0101] Comparative Example 4
[0102] Comparative Example 4 is different from Example 1 only in that the electrolyte in step (1.1) contains C 12 H 25 SO 4 Na concentration is 0.15 mol·L -1 , specifically including the following steps:
[0103] (1) Electrochemical deposition of copper deposit:
[0104] (1.1) Using 0.1 mol·L -1 CuSO 4 ·5H 2 O as raw material, and 0.1 mol·L -1NaCl, 0.05 mol·L -1 H 3 BO 3 , 0.15 mol·L -1 C 12 H 25 SO 4 Na and water together form the electrolyte for standby use;
[0105] (1.2) Select a flat copper substrate with a surface size of 10*10*1 mm (same as in Example 1), grind, polish, clean and dry it for later use;
[0106] (1.3) The copper substrate was used as the cathode and the copper foil was used as the anode. They were placed in the electrolyte. The power supply was fixed to the constant current mode. The deposition temperature was set to 30 °C and the stirring speed was set to 400 r·min. -1 , the current density was set to 20 mA·cm -2 Electrochemical deposition was carried out for 30 min, and the surface roughness of the copper deposit obtained was 50.23 nm and the thickness was 0.14 μm.
[0107] (1.4) The deposited copper substrate is cleaned and dried for later use.
[0108] (2) Preparation of tantalum transition layer by magnetron sputtering:
[0109] (2.1) Target pretreatment: The Ta target was installed in the first target position of the magnetron sputtering coating machine; the copper substrate treated in step (1) was fixed on the substrate table and then fixed on the sample trolley. The sputtering chamber was closed and low vacuum was first extracted. When the pressure in the sputtering chamber reached below 4 Pa, the molecular pump was started to extract high vacuum. When the vacuum in the sputtering chamber reached 5×10 -8 After Pa, argon gas is introduced for pre-sputtering to remove contaminants on the target surface;
[0110] (2.2) Coating: Adjust the gas pressure in the sputtering chamber, adjust the sputtering power of the Ta target to 300 W, the duty cycle to 90%, the bias voltage to -150 V, and the sputtering gas pressure to 0.5 Pa, and perform sputtering coating for 20 h (pause for cooling for 2 h every 5 h). After the sputtering is completed, turn off the magnetron and take out the substrate stage to obtain a copper substrate with a tantalum transition layer (thickness of 21 μm) deposited on it.
[0111] Example 2 (the transition layer is a multi-concentration V-Ta transition layer with a step-like increasing concentration)
[0112] The difference between Example 2 and Example 1 is that the transition layer is a multi-concentration V-Ta transition layer with a step-type increasing pattern, which is formed by stacking a low Ta concentration V-Ta film, a medium Ta concentration V-Ta film, and a high Ta concentration V-Ta film. Specifically, the Ta contents in the low Ta concentration V-Ta film, the medium Ta concentration V-Ta film, and the high Ta concentration V-Ta film are 15wt%, 50wt%, and 80wt%, respectively, and the thicknesses are 2 microns, 14 microns, and 5 microns, respectively.
[0113] The preparation method of the above transition layer is:
[0114] (a) The Ta target and the Ti target were installed on the two target positions of the magnetron sputtering coating machine respectively (the distance between the Ta target and the Ti target was 20 cm, and the distance between the Ta target and the Ti target and the injection port of the sputtering chamber was 50 cm and 70 cm respectively); the copper substrate was attached to the stainless steel plate and fixed on the mobile fixture trolley (the direction of the trolley's reciprocating movement was parallel to the straight line formed by the Ta target and the Ti target, and the distance was 20 cm; the starting point and end point of the reciprocating movement were flush with the Ta target and the Ti target respectively).
[0115] (b) Pre-sputtering: Close the sputtering chamber and evacuate the chamber to a pressure of ≥5×10 -4 Pa, and then argon gas was introduced for pre-sputtering for 5 min.
[0116] (c) Co-sputtering: Magnetron co-sputtering was performed, and the condition parameters of each stage were set as follows:
[0117] The duty cycle is 80%, the bias voltage is -150V, the sputtering gas pressure is 0.5Pa, the sputtering powers of the Ta target and the V target are adjusted to 50W and 300W respectively, and the mobile fixture trolley is controlled to move back and forth between the Ta target and the V target at a rate of 10mm / s. After coating, a low Ta concentration V-Ta film is formed.
[0118] Keeping other conditions unchanged, the sputtering powers of the Ta target and the V target were adjusted to 150 W and 150 W respectively, and the carriage speed was 15 mm / s to form a V-Ta film with a medium Ta concentration.
[0119] Keeping other conditions unchanged, the sputtering powers of the Ta target and the V target were adjusted to 400 W and 200 W respectively, and the carriage speed was 25 mm / s to form a high Ta concentration V-Ta film.
[0120] Example 3 (the transition layer is a linearly increasing multi-concentration V-Ta transition layer)
[0121] The only difference between Example 3 and Example 2 is that the transition layer is a multi-concentration V-Ta transition layer with a linearly increasing concentration, and the Ta content in the multi-concentration V-Ta transition layer increases linearly from 20wt% to 90wt% from the substrate to the target layer, and the total thickness of the transition layer is 21 microns (same as Example 2).
[0122] The preparation method of the above transition layer is:
[0123] (a) The Ta target and the Ti target were installed on the two target positions of the magnetron sputtering coating machine respectively (the distance between the Ta target and the Ti target was 20 cm, and the distance between the Ta target and the Ti target and the injection port of the sputtering chamber was 50 cm and 70 cm respectively); the copper substrate was attached to the stainless steel plate and fixed on the mobile fixture trolley (the direction of the trolley's reciprocating movement was parallel to the straight line formed by the Ta target and the Ti target, and the distance was 20 cm; the starting point and end point of the reciprocating movement were flush with the Ta target and the Ti target respectively).
[0124] (b) Close the sputtering chamber and evacuate the chamber until the pressure is ≥5×10 -4 Pa, and then argon gas was introduced for pre-sputtering for 5 min.
[0125] (c) Co-sputtering: magnetron co-sputtering was performed with the following parameters: the duty cycle was adjusted to 80%, the bias voltage was -150 V, and the sputtering gas pressure was 0.5 Pa; the initial sputtering power of the Ta target was adjusted to 50 W, the power increase rate was 60 W / h, and the initial sputtering power of the V target was adjusted to 150 W, the power increase rate was 30 W / h. Magnetron co-sputtering was performed in an inert atmosphere, and the mobile fixture carriage was controlled to move back and forth between the Ta target and the V target at an initial speed of 10 mm / s and a speed increase of 2 mm / h. After coating, a multi-concentration V-Ta transition layer was formed.
[0126] Performance comparison
[0127] The performance tests were performed on the samples obtained from the above embodiments and comparative examples, and the results are shown in the following table:
[0128]
[0129] Through the analysis of the above data and Figure 6 By comparison, we can see that:
[0130] Compared with comparative example 1, in Example 1, a copper deposition layer is deposited on the surface of the copper substrate by an electrochemical process in advance. The results show that the film stress in the sample obtained in Example 1 is significantly lower than that in comparative example 1, which indicates that the presence of the copper deposition layer can significantly reduce the film stress of the transition layer and improve the coating effect at the same time.
[0131] Furthermore, compared with Example 1, the difference between Comparative Example 2 and Comparative Example 3 is that the electrolyte contains CuSO 4 ·5H2 O concentrations are higher and lower in the electrolyte of the present invention, CuSO 4 ·5H 2 O is the main salt of the electrochemical deposition solution, providing the main metal ions. The results show that when CuSO 4 ·5H 2 When the concentration of CuSO is high (Comparative Example 2), the copper deposition rate tends to be fast, which will lead to a decrease in the bonding strength of the coating; 4 ·5H 2 When the O concentration is too low (Comparative Example 3), the coating will be burned, thus affecting the coating effect of the subsequent transition layer.
[0132] Comparative Example 4 is compared with Example 1 in that the electrolyte contains C 12 H 25 SO 4 The concentration of Na is high. 12 H 25 SO 4 As an additive, Na can accelerate the deposition of metallic copper ions through the synergistic effect with chloride ions, and can refine the grains, making the coating bright and delicate. However, if too much is added, the coating will become white and brittle, and will also affect the coating effect of the subsequent transition layer.
[0133] On the other hand, compared with Example 1, the difference between Examples 2-3 is that the transition layer uses a multi-concentration V-Ta transition layer with a linear increase and a step increase. The results show that compared with Example 1 using a pure tantalum transition layer, the film stress can be further reduced.
[0134] Example 4
[0135] The only difference between Example 4 and Example 1 is that in step (1.1), the copper substrate is replaced by a grid-shaped copper substrate (size is 10*10*0.1 mm, 200 mesh, such as Figure 7 as shown).
[0136] After the copper deposit layer is deposited on the surface of the grid-shaped copper substrate according to the electrochemical process of Example 1, the photo is as follows Figure 8 As shown, it can be found that copper ions are uniformly deposited on the surface of the copper mesh and cover the inside of the mesh, indicating that the electrochemical deposition process of the present invention is applicable to copper substrates with special surface morphology, and is more versatile than traditional mechanical roughening methods such as sandblasting.
[0137] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0138] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an accelerator neutron source lithium target transition layer by electrodeposition-magnetron sputtering, characterized in that: include: 1) The copper substrate is used as the cathode and the copper sheet is used as the anode, and is placed in an electrolyte containing copper ions for electrochemical deposition to form a copper deposition layer with a roughness of 40-100 nm and a thickness of 0.05-0.5 μm on the surface of the copper substrate; The electrolyte includes 0.05-0.1 mol / L CuSO4·5H2O, 0.05-0.1 mol / L NaCl, 0.01-0.1 mol / L H3BO3, 0.01-0.1 mol / L 12 H 25 SO4Na and water; 2) Constructing a transition layer on the surface of the copper deposited layer by magnetron sputtering.
2. The method according to claim 1, characterized in that: 1), the copper substrate is pre-ground, polished, cleaned and dried.
3. The method according to claim 1, characterized in that: 1), the conditions of the electrochemical deposition are: the power supply is in constant current mode, the deposition temperature is 25-40°C, and the stirring speed is 200-600 r·min -1 , the current density is 15-25 mA·cm -2 , the deposition time is 20-40 min.
4. The method according to claim 1, characterized in that: 1), the copper substrate is cleaned and dried after electrochemical deposition.
5. The method according to claim 1, characterized in that: 2), the transition layer is a multi-concentration V-Ta transition layer; in the multi-concentration V-Ta transition layer, the Ta content increases stepwise in the range of 10-100wt% from the copper substrate to the target layer, and the preparation method thereof comprises: S1: Fix the Ta target and V target on the target position; fix the copper substrate on the trolley; S2: The sputtering powers of the Ta target and the V target are adjusted to 50-100W and 100-300W respectively, and magnetron co-sputtering is performed in an inert atmosphere. The trolley is controlled to move back and forth between the Ta target and the V target at a rate of 10-15mm / s to form a low Ta concentration V-Ta film; S3: adjusting the sputtering powers of the Ta target and the V target to 100-300W and 100-300W respectively, and the trolley speed to 15-20mm / s, to form a V-Ta film with a medium Ta concentration; S4: The sputtering powers of the Ta target and the V target are adjusted to 300-600W and 100-300W respectively, and the carriage speed is 20-25mm / s to form a high Ta concentration V-Ta film.
6. The method according to claim 1, characterized in that: 2), the transition layer is a multi-concentration V-Ta transition layer; in the multi-concentration V-Ta transition layer, the Ta content increases linearly in the range of 10-100wt% from the copper substrate to the target layer, and the preparation method thereof comprises: S1: Fix the Ta target and V target on the target position; fix the copper substrate on the trolley; S2: Adjust the initial sputtering power of the Ta target to 50-100W, the power increase rate to 50-100W / h, the initial sputtering power of the V target to 100-300W, the power increase rate to 20-50W / h, and perform magnetron co-sputtering under an inert atmosphere. Control the trolley to move back and forth between the Ta target and the V target at an initial rate of 10-15mm / s and an increase rate of 1.5-2.5mm / h to form a multi-concentration V-Ta transition layer.
7. The method according to claim 5 or 6, characterized in that: The thickness of the multi-concentration V-Ta transition layer is 15-40 microns.
8. The method according to claim 5, characterized in that: In a step-by-step manner, the Ta contents in the low Ta concentration V-Ta film, the medium Ta concentration V-Ta film and the high Ta concentration V-Ta film are 10-30wt%, 30-60wt% and 60-90wt% respectively.
9. The method according to claim 5, characterized in that: The thickness of the low Ta concentration V-Ta film is 1-2 microns, the thickness of the medium Ta concentration V-Ta film is 10-15 microns, and the thickness of the high Ta concentration V-Ta film is 3-9 microns.
Citation Information
Patent Citations
Corrosion-resistant super-hydrophobic copper-nickel composite coating and preparation method and application thereof
CN114790563A
High-binding-force multi-gradient target system and preparation method thereof
CN118450586A